(х - у - 2 = 0, (2х - 3у + 1 = 0; (-х+у-4=0, (4х+у+1=0; (3х+у-4=0, (5х+у-10=0.
РЕШИТЕ

t0l1k t0l1k    3   03.05.2020 18:42    0

Ответы
islamovaemilia1 islamovaemilia1  14.10.2020 06:21

Відповідь:

Покрокове пояснення:

\left \{ {{x-y-2=0} \atop {2x-3y+1=0}} \right.

x-y-2=0\\x=0+y+2\\x=y+2\\x=1+2\\x=3                2x-3y+1=0\\2(y+2)-3y+1=0\\2y+4-3y+1=0\\2y-3y=0-4-1\\-y=-5\\y=-5:(-1)\\y=1

\left \{ {{-x+y-4=0} \atop {4x+y+1=0}} \right. \\

-x+y-4=0\\y=0+x+4\\y=x+4\\y=-1+4\\y=3             4x+y+1=0\\4x+(x+4)+1=0\\4x+x+4+1=0\\4x+x=0-4-1\\5x=-5\\x=-5:5\\x=-1

\left \{ {{3x+y-4=0} \atop {5x+y-10=0}} \right.

3x+y-4=0\\y=0-3x+4\\y=-3x+4\\y=-3*3+4\\y=-9+4\\y=-5                    5x+y-10=0\\5x+(-3x+4)-10=0\\5x-3x+4-10=0\\5x-3x=0-4+10\\2x=6\\x=6:2\\x=3

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика